(untitled) (CAHIERS MAGELLANES-NS, 2024)
yslipidemia is a major risk factor for cardiovascular disease (CVD) and is linked to high levels of low-density lipoprotein cholesterol (LDL-C) and triglycerides, as well as low levels of high-density lipoprotein cholesterol (HDL-C). It's important to effectively manage dyslipidemia for the primary prevention of CVD. Homeopathy offers a promising complementary approach to tackle this challenge, focusing on personalized treatment and holistic patient care. This abstract presents an enhanced intervention plan and protocol for the homeopathic management of dyslipidemia, placing emphasis on early prevention of cardiovascular disease risk. The proposed intervention plan integrates traditional homoeopathic principles with recent advances in understanding lipid metabolism and cardiovascular health. Key elements include individualized remedy selection based on a comprehensive patient assessment, incorporating both clinical symptoms and constitutional factors. The protocol aims to reduce the LDL-C and triglycerides, improve HDL-C levels, and address underlying metabolic imbalances that contribute to dyslipidemia. This plan also incorporates lifestyle modifications such as diet, physical activity, and stress management as part of a holistic treatment strategy. The efficacy of specific homoeopathic remedies, such as Allium sativum, Crataegus oxyacantha, and Lycopodium clavatum, is highlighted, along with their potential to modulate lipid profiles and prevent the progression to cardiovascular complications. By improving the treatment protocol, this approach aims to enhance patient outcomes, decrease cardiovascular risk factors, and offer a sustainable, non-invasive option for managing dyslipidemia. Further clinical trials and studies are necessary to support these findings and refine the homeopathic treatment protocol for broader application in preventive cardiovascular care.